Association of Vocal Fatigue and Years of Experience in practicing Speech and Language Pathologists: Association of Vocal Fatigue and Years of Experience in Pathologists - Ijaz, Aneesa; Yaqoob, Saba; Mansoor, Abiha Fatima; Aziz, Saba; Masood, Fahad (Pakistan Journal of Health Sciences, 2022)
SLPs (Speech and Language Pathologists) are healthcare specialists that specialize in the areas of swallowing and communication across the lifespan. While communication comprises speech production, language, fluency, voice, hearing, cognition, resonance and swallowing involves all aspects of swallowing, including related feeding habits. According to the definition of vocal fatigue, it is "the perception of voice user, manifested mostly as an increased vocal effort that develops over time with voice usage and reduces with voice rest." Objective: To explore an association of vocal fatigue and years of experience among practicing Speech and Language Pathologists. Methods: A cross-sectional study was held with sample size of 80 participants’ using quota sampling technique. Vocal Fatigue Index questionnaire was used to collect data from SLP’s which consists of 19 items having factor 1 (tiredness of voice), factor 2 (physical discomfort) and factor 3 (improvements of symptoms with rest). Results: The mean score of tiredness of voice (factor 1) was 20.15 ± 7.18 having Pearson correlation of 0.470, mean score of physical discomfort (factor 2) was 8.30 ± 4.156 having Pearson correlation of 0.393 and the mean score of improvement of symptoms with rest (factor 3) was 7.86 ± 2.814 having Pearson correlation of -0.063. The mean year of experience was 2.38 ± 1.49. Conclusions: As the age of Speech Language Pathologist increased, they become more experienced but they decreased their workload by reducing their medical practices in this way their vocal fatigue decreases automatically. Hence as the years of experience increases the vocal fatigue of SLP’s decreases.